Carbon supports and synthesis of palladium catalysts supported on them - Ali Hussein Al-Wadhaf (Тонкие химические технологии, 2012)
This review is devoted to the synthesis of palladium heterogeneous catalysts on carbon supports. The review consists of three parts. In the first part different types of carbon supports are explored. The second part is devoted to methods of activation of carbon supports, and in the third part methods of preparation of palladium catalysts supported on carbon are investigated.